The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1164/rccm.201308-1414oc
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure to Air Pollution and Lung Function in the Framingham Heart Study

Abstract: Rationale: Short-term exposure to ambient air pollution has been associated with lower lung function. Few studies have examined whether these associations are detectable at relatively low levels of pollution within current U.S. Environmental Protection Agency (EPA) standards. Objectives: To examine exposure to ambient air pollutants within EPA standards and lung function in a large cohort study. Methods: We included 3,262 participants of the Framingham Offspring and Third Generation cohorts living within 40 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
103
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(114 citation statements)
references
References 49 publications
9
103
2
Order By: Relevance
“…Numerous reports have also found that shortterm (1-3 days) increases in PM 2.5 are associated with decreases in lung function in healthy subjects and in those with preexisting pulmonary diseases such as asthma or chronic obstructive pulmonary diseases (Cakmak et al, 2011;Rice et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have also found that shortterm (1-3 days) increases in PM 2.5 are associated with decreases in lung function in healthy subjects and in those with preexisting pulmonary diseases such as asthma or chronic obstructive pulmonary diseases (Cakmak et al, 2011;Rice et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Air quality has been, for many years, a focus of attention because of its harmful effects on human health and the environment (e.g., Curtis et al, 2006;Sanderson et al, 2006;Rice et al, 2013). New estimates released by World Health Organization (WHO) report that in 2012 around 7 million people died e one in eight of total global deaths e as a result of air pollution exposure, including almost 600,000 in the WHO European Region.…”
Section: Introductionmentioning
confidence: 99%
“…Framingham Heart Study, we recently found that short-term increases in exposure to fine particulate matter less than 2.5 mm in aerodynamic diameter (PM 2.5 ), ozone, and nitrogen dioxide (NO 2 ) at concentrations below the Environmental Protection Agency National Air Quality Standards were associated with a lower FEV 1 and FVC in nonsmoking adults (6). It remains unclear whether long-term exposure to traffic emissions and fine particulate matter (PM 2.5 ) at relatively low levels in the United States affects lung function in healthy adults.…”
mentioning
confidence: 99%